The influence of estro-progestin therapy on neurohormonal activity in functional hypothalamic amenorrhea. (2nd November 2022) - Szeliga, Anna; Podfigurna, Agnieszka; Bala, Gregory; Meczekalski, Blazej
Abstract: Background: Functional hypothalamic amenorrhea (FHA) is a chronic endocrine disorder caused by the abnormal pulsatile secretion of neurohormones in the hypothalamus. Secretion of GnRH is regulated by kisspeptin/neurokinin B/dynorphin (KNDy) neurons. These neurons produce, among other neurohormones, neurokinin B (NKB) which regulates the coordinated stimulation or inhibition of GnRH secreting neurons. Aim of the study: Assessment and comparison of serum NKB in patients with FHA at baseline, and following 6 months of estrogen-progestagen therapy. Materials and methods: Fifty-five patients with functional hypothalamic amenorrhea were included in the study group. Serum concentrations of neurokinin B (NKB), follicle stimulating hormone (FSH), luteinizing hormone (LH), 17-β-estradiol (E2), prolactin (PRL), cortisol, testosterone (T), dehydroepiandrosterone sulfate (DHEA-S), thyroid-stimulating hormone (TSH), free thyroxine (fT4), fasting glucose and insulin, as well as lipid profile were measured at baseline. At the time of diagnosis, patients with FHA were prescribed a course of 2 mg 17-β-estradiol and 10 mg dydrogesterone for duration of 6 months. Serum NKB was then reassessed following treatment at 6 months. Results: At baseline, the FHA group was found to have a decreased serum NKB concentration when compared to a healthy control group. Following 6 months of sequential estrogen-progestogen hormone therapy, this study did not find any statistically significant difference in serum NKB concentration in the treatment arm compared to baseline. Conclusions: For the first time, NKB secretion has been studied in patients with FHA. A significantly lower level of serum NKB was observed in these patients at baseline, when compared to a control group. After 6 months of combination estrogen-progesterone therapy, no significant changes in NKB levels were observed in these patients. These findings, for the first time in the literature, provide insight into the perceived benefit of HRT, calling into question its benefit in addressing the underlying etiopathogenetic contributors of FHA. These new findings may contribute to more targeted and appropriate treatment of such patients in the future.